Reforma administracji jako podstawa prowadzenia polityki regionalnej oraz element dostosowania organizacji terytorialnej Polski do standardów Unii Europejskiej - Sawicka, Janina; Calak, Renata (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
A major issue in the field of Polish economy and policy adjustment into the European Union standards constitutes decentralisation of governance introduced by State Administration Reform that was entered into force on 1 January 1999. The reform replaced existing structures by devolving powers to three levels of self-government at regional (16 Voivodships), county (308 Poviats plus 65 city Poviats) and commune (2489 Gminas) levels. The European Union supports the process of Central and Eastern European Countries integration with the Communities devoting its funds through special programmes as PHARE-2 and two new pre-accession funds: ISPA and SAPARD. The key priority areas in providing applicant countries with sources from these funds are: natural environment protection, transport network development and supporting the stable and sustainable development of rural areas.